CIFOR’s strategy for collaborative forestry research - Center for International Forestry Research (Center for International Forestry Research, 1996)
Pressures on the remaining forests to provide ever-increasing volumes of fuelwood, timber, non-timber products, watershed protection and land for agriculture and other purposes keep growing. At the same time, the importance of tropical forests to the well-being of the rural poor, in regulating the global climate and as a reservoir of biodiversity is increasingly recognised. With growing social recognition of the many diverse values of forests, the dominant demand is likely to change from timber, to providing a much wider range of social, economic and environmental benefits, for a much wider range of beneficiaries. Some forests will be more valuable for environmental and watershed protection, or for provision of non- timber products to local communities, than for their capacity to produce industrial wood-fibres. CIFOR works through research partnerships, as a "Center without Walls" with a holistic, inter-disciplinary approach to solving general or widespread problems. CIFOR's strategic research is focused on policy issues that will enable more informed, productive, sustainable and equitable decisions about the management and use of forests. CIFOR will give priority to research at seven focal ecological regions: the tropical moist forests in central-west Africa and the Congo; the drier forests (like the Miombo woodlands) of eastern-southern Africa); the rainforest-dry forest continuum in southern India (such as the Western Ghats); the tropical moist forests in insular Southeast Asia (e.g. Borneo); the uplands of mainland Southeast Asia; the tropical moist forests of the western Amazon; and the mixed forest systems of Central America.